Spatial structuring of bacterial communities in epilithic biofilms in the Acquarossa river (Italy). Issue 12 (10th September 2018) - Chiellini, Carolina; Miceli, Elisangela; Bacci, Giovanni; Fagorzi, Camilla; Coppini, Ester; Fibbi, Donatella; Bianconi, Giovanna; Mengoni, Alessio; Canganella, Francesco; Fani, Renato
ABSTRACT: Epilithic river biofilms characterize the rock surfaces along the Acquarossa river (Viterbo, Italy); they are in part red and in part black colored, maintaining a well-defined borderline. This peculiarity has raised questions about the biotic and abiotic phenomena that might avoid the mixing of the two biofilms. In this study, the structuring of bacterial communities in black and red epilithic biofilm in the Acquarossa river has been investigated with both culture dependent and independent approaches. Data obtained highlighted a (very) different taxonomic composition of black and red epilithons bacterial communities, dominated by Acinetobacter sp. and iron-oxidizing bacteria, respectively. The chemical characterization of both river water and biofilms revealed a substantial heavy metals pollution of the environment; heavy metals were also differentially accumulated in red and black epilithons. Overall, our data revealed that the structuring of red and black epilithons might be affected mainly by the antagonistic interactions exhibited by bacterial genera dominating the two biofilms. These findings suggest that biotic factors might be responsible for the structuring of natural bacterial communities, suggesting that there is a selection of populations at very small scale, and that different populations might compete for different niches. Abstract : Structure of bacterial communities in black and red epilithic biofilm in the Acquarossa river (Viterbo, Italy) has been investigated with both culture dependent and independent approaches.